Design and Testing of a Whole-Row Top-Loosening Stem-Clamping Seedling Extraction Device for Hole Tray Seedlings - Zehui Peng; Fazhan Yang; Yuhuan Li; Xiang Li; Baogang Li; Guoli Xu (Agriculture)
A combined seedling extraction device was developed that operates by first top loosening and then clamping the stem in order to solve the current issues with automated transplanting technology, such as low seedling extraction efficiency and a high rate of substrate loss. The pepper plug tray seedlings were selected as the experimental subjects for testing the mechanical properties of the stems. The tensile and compressive mechanical properties of the stems were obtained, and the kinematic model of the seedling spacing process and the mechanical model of the seedling clamping process were established. Key parameters of the seedling extraction device were analyzed and calculated, and an automated seedling extraction system was constructed. Using substrate moisture content, seedling age, and extraction frequency as experimental factors, orthogonal tests were conducted. Through variance analysis and 3D response surface analysis, the optimal rounded parameter values were determined: 48% substrate moisture content, 38-day-old seedlings, and a seedling extraction frequency of 60 plants/min. Under these conditions, the seedling extraction success rate was 94.44%, the substrate loss rate was 6.07%, and the seedling damage rate was 4.17%, meeting the requirements for automated seedling extraction.